Acoustodynamic transformation of the defect structure in Hg₁₋xCdx Te alloys - Olikh, Y.M.; Savkina, R.K.; Vlasenko, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The results of the investigations of transport properties of n- and p-Hg₁₋xCdxTe semiconductor crystals exposed to intensive ultrasound (≈ 6MHz) are represented. Acousto-stimulated phenomena of concentration change (increase in n-type and decrease in p-type) are observed in the region of impurity conductivity. The possible mechanism of the acousto-dynamic processes (electrical activation/disactivation of the crystals defects) are analyzed. For the first time the phenomenon of acoustostimulated p®n conversion have been detected in p-Hg₁₋xCdxTe at T < 120 K. The results of the investigations of transport properties of n- and p-Hg₁₋xCdxTe semiconductor crystals exposed to intensive ultrasound (≈ 6MHz) are represented. Acousto-stimulated phenomena of concentration change (increase in n-type and decrease in p-type) are observed in the region of impurity conductivity. The possible mechanism of the acousto-dynamic processes (electrical activation/disactivation of the crystals defects) are analyzed. For the first time the phenomenon of acoustostimulated p→n conversion have been detected in p-Hg₁₋xCdxTe at T < 120 K.